Analisis Pendapatan Usahatani Padi dan Bunga Pacar Air di Subak Munduk Sepit, Desa Sibang Gede, Kecamatan Abiansemal, Kabupaten Badung - IDAYANTI, I GUSTI AYU ADE; DARMAWAN, DWI PUTRA; YUDHARI, I DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Analysis Of Income For Rice and Water Henna Flower Farming  In Subak Munduk Sepit,  Sibang Gede Village, Abiansemal District, Badung Regency.  Indonesia well known as agrarian country which means Indonesia rely on the agricultural sector as a source of livelihood. The accomplishment in farming (the amount of farmer’s income) is affected by farm production factors such as capital, land, and labor. This research was to determine the average income of rice and henna flower farming activity and also analyze the difference in income average between them at Subak Munduk Sepit, Sibang Gede, Abiansemal, Badung. Based on the research conducted, several things can be found as a result of the research. The obtained finding’s were: 1) the average net income of rice farming with an average production yield of 5819.14Kg/Ha/planting season is Rp18,281,452.13/Ha 2) the net income of water henna flower farmers with an average production yield of 158,769.64Kg/Ha/planting season is Rp81,464,479.64/Ha 3) Based on the t-test analysis, the significance value is 0.000 <0.05, which means that there is a significant difference in income between rice farmers and henna flowers.